CircSCUBE3 promoted ferroptosis to inhibit lung adenocarcinoma progression: CircSCUBE3 inhibits LUAD - Fu, Hongye; Zhao, Qiong (Cellular and Molecular Biology, 2024)
CircRNAs can regulate ferroptosis and affect cancer development and are promising biomarkers and therapeutic targets in lung cancer. circSCUBE3 is expressed in lung adenocarcinoma (LUAD) tissues. In this study, our purpose was to study the role and regulatory mechanism of circSCUBE3 in LUAD ferroptosis. circSCUBE3 was identified to be significantly downregulated in LUAD samples and cell lines. The expression of biomarkers related to lipid oxidation (4-HNE) and ferroptosis (Ptgs2) was both downregulated in LUAD tissues, suggesting the ferroptosis resistance in LUAD. Erastin, a ferroptosis inducer, was used to stimulate the LUAD cells for 48 h. The cell viability, 4-HNE and Ptgs2 level of LUAD cells were decreased by exposure to erastin while the expression of circSCUBE3 was not significantly altered. We then overexpressed circSCUBE3 in LUAD cells and found it decreased the GSH level and GSH/GSSG ratio in LUAD cells. CircSCUBE3 might serve as an independent factor of ferroptosis and may induce ferroptosis in LUAD by inhibiting GSH synthesis. The loss-of-function experiments were conducted, and circSCUBE3 deficiency reversed the erastin-induced reduction in cell viability, GSH level, GSH/GSSG ratio, mitochondrial membrane potential and elevation in MDA content, Ptgs2, 4-HNE expression as well as lipid ROS production. CircSCUBE3 negatively regulated GPX4 expression in LUAD cells, and the silencing of GPX4 counteracted the impact of circSCUBE3 deficiency on LUAD cell viability as well as ferroptosis, suggesting that circSCUBE3 regulated the GPX4-mediated GSH synthesis in LUAD. CircSCUBE3 was to bind to CREB, which activated the transcription of GPX4. CircSCUBE3 negatively regulated GPX4 expression by competitively interacting with CREB. In the tumor-bearing mouse models, circSCUBE3 silencing promoted tumor growth and reversed the erastin treatment-induced inhibition on tumorigenesis in vivo. In conclusion, circSCUBE3 inhibited LUAD development by promoting ferroptosis via the CREB/GPX4/GSH axis, which might provide a novel option for the LUAD targeted therapy.